Hazardless nanocomposite for gas barrier potential - Jamal, Nur Ayuni; Anuar, Hazleen; Ahmad, Zuraida; Abd Razak, Shamsul Bahri (2010)
Composites based on high density polyethylene (HDPE), ethylene propylene diene monomer (EPDM) and Organically Modified Montmorillonite (OMMT) clays were made by melt compounding followed by compression molding. Tensile testing, X-ray diffraction (XRD) and Transmission Electron Microscopy (TEM) were used to characterize the nanocomposites. The addition of clay, compatibilizer agent (Maleic Anhydride Polyethylene (MAPE)) and the exposure under Electron Beam Irradiation (EB) considerably improved the tensile properties of the composite system. Tensile Strength (MPa) and Tensile Modulus (MPa) were found to increase significantly with increasing clay content and decreasing as the clay content exceeds 4 wt% values. The largest improvement in composite mechanical properties occurred at clay loading levels of 4% (2-8 wt %) with EB Irradiation system followed by MAPE and unirradiated/untreated systems. Nearly 67% increase in tensile strength and 64% increase in tensile modulus were observed with EB irradiated system. The d spacings of the clay in nanocomposite were monitored using XRD and the extent of delamination was examined by TEM. The wide angle of XRD patterns showed the increased d-spacing of clay layers, indicating enhanced compatibility between HDPE and OMMT with the EB irradiated and addition of MAPE. TEM photomicrographs illustrated the intercalated and partially exfoliated structures of the nanocomposite with OMMT and MAPE system.